Praktik Sosial antara Orang dengan Masalah Kejiwaan dengan Relawan Griya Schizofren di Griya PMI (Palang Merah Indonesia) Peduli Surakarta: Social Practices between Individuals with Mental Illness and Griya Schizofren Volunteers in Griya PMI (Indonesian Red Cross) Peduli Surakarta - Triana Rahmawati; Drajat Tri Kartono; Trisni Utami; Yuanita Dwi Hapsari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This research discusses the social practices carried out by Griya Schizofren to address individuals with mental illness who are often disadvantaged due to the negative stigma of their illness. This research uses a phenomenological approach. Data were collected from observations, interviews, and documentation. The results show that Griya Schizofren, to reduce the stigma against individuals with mental illness, established social, economic, cultural, and symbolic relations with those who lived in Griya PMI Peduli (Indonesian Red Cross) Surakarta through voluntary activities for individuals with mental illness. Social welfare activities in individuals with mental illness had shifted to business activity that opened a new field. The habitus of individuals with mental illness positively developed. Griya Schizofren restructured individuals with mental illness in a new layer of the community by promoting it as a society that can work within its limitations and produce products demanded by the community in the form of wedding souvenirs. Field of Griya PMI Peduli became a more humane environment as the shelter for abandoned individuals with mental illness. It also proved that total institution is no longer a frightening but collaborative field for capital exchange. Hence, using the theory of Piere Bourdieu, this research can answer how the stigma can be unfolded through works and capital exchange.